Effect of sex and reproductive status on the immunity of the temperate bat Myotis daubentonii - Ruoss, Sara (Mamm Biol, 2018)
Studies of immunity in bat species are rare. However, it is important to determine immunological variations to identify factors influencing the health status of these endangered mammals from an evolutionary, ecological, conservation, and public health point of view. Immunity is highly variable and can be influenced by both internal (e.g. hormone levels, energy demand) and external factors (e.g. pathogens, climate). As bats have some peculiar ecological, energetic, and putative immunological characteristics, they are outstanding study organisms for ecoimmunological studies. We tested if (i) female bats have a higher immunity than males similar to most other mammalian species and (ii) individuals differ according to their energy demand (e.g. reproductive status). To study these questions, we sampled female and male Myotis daubentonii with different reproductive states and estimated their bacterial killing activity, hemolysis/hemagglutination titer, immunoglobulin G (IgG) concentration, and total and differential white blood cell counts. These methods characterize the cellular and humoral branches of both the adaptive and the innate immune responses of these individuals. Reproductively active males had lower cellular immunity compared to non-reproductive individuals. Pregnant females had increased IgG concentrations while hemolysis was enhanced during lactation. No clear trade-off between immunity and reproduction was found; instead immunity of males and female bats seems to be modulated differently due to varying hormonal and energetic states. Our data suggest that both adaptive and innate immunity as well as individual differences (i.e. sex and reproductive state) need to be considered to get a comprehensive overall picture of immunity in wild mammals.